2016
DOI: 10.1016/j.pmedr.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sport participation: A systematic review of the impact of fatherhood

Abstract: Moderate to Vigorous Physical Activity (MVPA), including sport participation, is an important component of a healthy lifestyle. Scholars have devoted considerable attention to understanding the impact of parenthood on MVPA, albeit only for women. As the impact of fatherhood on men's lives is drawing more and more scholarly and societal attention, the aim of the current article is to provide an systematic overview of studies examining the impact of fatherhood on MVPA.A systematic review was conducted in Google … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 48 publications
3
45
2
Order By: Relevance
“…However, our estimate is also slightly smaller than estimates of weight gain with parity in Australian women, stating that women with one baby gained 4 kg more than single childless women over 10 years . Previous reviews of physical activity and parenthood have compared activity levels between parents and non‐parents rather than examining change over the transition of becoming a parent . Both previous reviews concluded that parents were less active than non‐parents and more specifically that fathers of young children spent less time in MVPA, but not sport, than childless men .…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…However, our estimate is also slightly smaller than estimates of weight gain with parity in Australian women, stating that women with one baby gained 4 kg more than single childless women over 10 years . Previous reviews of physical activity and parenthood have compared activity levels between parents and non‐parents rather than examining change over the transition of becoming a parent . Both previous reviews concluded that parents were less active than non‐parents and more specifically that fathers of young children spent less time in MVPA, but not sport, than childless men .…”
Section: Discussioncontrasting
confidence: 62%
“…Previous reviews of physical activity and parenthood have compared activity levels between parents and non‐parents rather than examining change over the transition of becoming a parent . Both previous reviews concluded that parents were less active than non‐parents and more specifically that fathers of young children spent less time in MVPA, but not sport, than childless men . Reviews examining diet during early adulthood have shown mixed longitudinal patterns, which differed by dietary outcome, with sugar consumption decreasing between late adolescence and early adulthood .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus group gave families the opportunity to add context to their accelerometer data. To date, mostly objective data has been used to characterise children’s [ 45 ], parents’ [ 46 ], and parent–child PA [ 47 , 48 , 49 ]. It became evident in the focus group that some of the objective PA estimates may have been biased due to legitimate monitor non-wear and the inability of the accelerometers to capture water-based (i.e., swimming) and cycling activities [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 After having children, men's physical activity levels generally reduce. [15][16][17] Evidence of the effectiveness of weight management programmes for men…”
Section: Chapter 1 Introductionmentioning
confidence: 99%